Diferencias semánticas entre los distintos tipos de completivas declarativas - Sánchez Salor, Eustaquio (1991)
The semantic solution to the question concerning the difference between the various ypes of declarative nominal subordinate clauses would be as follows: clauses which are normally constructed with infinitive only, dico Caesarem uenire, from the semantic point of view contain only the feature [+ QUID], that is, they indicate only the quidditas or content of the declarative verb. Clauses constructed with quod, doleo quod non venias, contain the feature [+ QUID] —indicating, in effect, the content of the affliction— and allo the feature [UNDE] since they indicate also the engin or starting point of the affliction. Finally, those clauses constructed with ut + subjunctive, such as accidit ut omnes deicerent, like all nominal subordinate clauses contain the feature (+QUID], given that they indicate the quidittas of the occurrence, as well as the feature [+QUOD], since they indicate ah° de end result produced by the situa- tion in question.
Keywords: Semántica